2007
DOI: 10.7202/032355ar
|View full text |Cite
|
Sign up to set email alerts
|

Le rôle de l’émotion exprimée dans le cours de la schizophrénie

Abstract: RÉSUMÉ Au cours d'une décennie consacrée à d'abondantes recherches sur le cerveau, une avenue s'est, entre autre, ouverte pour démontrer l'importance de prendre en ligne de compte les facteurs psychosociaux dans le cours de la schizophrénie. Le but de cet article est de décrire brièvement le concept « d'émotion exprimée » qui s'est souvent révélé utile comme facteur de prévisibilité de la rechute dans différents types de maladies mentales graves. Nous y décrirons également un programme de recherches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Various studies have indicated that social support provided by relatives helped prevent hospitalization or at least diminish its length due to prompter intervention (Carpentier et al 1999;Becker et al 1997;Albert et al 1998). Other studies have concluded that relapse was not associated with the amount of contact with high familial expressed emotions (King and Rochon 1995;King and Dixon 1999), but related more closely to the severity of the disorder. Conversely, other previous works have highlighted the fact that lengthy hospitalizations, more common among GwithoutF patients, tend to sever family or social networks (Browne and Courtney 2007;Angel and Test 2002;Kaiser 2000); more acute disorders and co-morbidity with drugs may also alienate families.…”
Section: Discussionmentioning
confidence: 94%
“…Various studies have indicated that social support provided by relatives helped prevent hospitalization or at least diminish its length due to prompter intervention (Carpentier et al 1999;Becker et al 1997;Albert et al 1998). Other studies have concluded that relapse was not associated with the amount of contact with high familial expressed emotions (King and Rochon 1995;King and Dixon 1999), but related more closely to the severity of the disorder. Conversely, other previous works have highlighted the fact that lengthy hospitalizations, more common among GwithoutF patients, tend to sever family or social networks (Browne and Courtney 2007;Angel and Test 2002;Kaiser 2000); more acute disorders and co-morbidity with drugs may also alienate families.…”
Section: Discussionmentioning
confidence: 94%
“…Des résultats récents forcent à mettre en doute l'hypothèse selon laquelle un degré d'ÉE élevé provoque une détérioration clinique chez des personnes atteintes de schizophrénie (King et Rochon, 1995) et évo-quent plutôt une interaction entre l'état clinique de l'individu, le contexte et la réaction de la famille.…”
Section: Les Personnes Atteintes De Schizophrénie Et Le Stressunclassified